John Steinbeck in Lyme Regis - Unknown:::Creator:::::::::::: (England; Somerset, 2022)
John Steinbeck in Lyme Regis a town by the English Channel in west Dorset, England, 25 miles (40 km) west of Dorchester. It has noted fossils in cliffs and beaches on the Heritage or Jurassic Coast, a World Heritage Site.